2000
DOI: 10.17986/blm.200051382
|View full text |Cite
|
Sign up to set email alerts
|

Hukukçuların ve Polislerin Irza Geçme ile İlgili Ceza Sistemine Bakış Açılarının Değerlendirilmesi

Abstract: E v a lu a tio n o f J u r i s t s a n d P o lic e O f f ic e r s V iew s A b o u t J u d i c i a l P r o c e s s a n d L aw s R e la te d w i t h R a p e C a s e s Z . B e lm a GÖLGE*, M. F a t i h YAVUZ**, T a n d M. BAŞKAN ***. G ölge ZB, Yavuz MF, B a ş k a n TM. H u ku kçu ların ve polislerin ır z a g eçm e ile ilgili cez a sistem in e bakış ÖZETIrza geçm e hukuki, tıbbi, psikolojik ve sosyal boyutlar içersinde değerlendirildiğinde cinayetten sonra insan bede nine karşı yapılan en ağır saldırılardan biri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Different studies have shown that these myths are also widely accepted in our country (Gölge, 1997;Sakallı-Uğurlu et al, 2007;Yılmaz & Oskay, 2019;Karaman, 2022). Men's efforts to justify sexual violence and women's efforts to make it accepted that they are strong is a special function of myths (Çamaş &Mete, 2016;Yılmaz &Oskay, 2022).…”
Section: Introductionmentioning
confidence: 94%
“…Different studies have shown that these myths are also widely accepted in our country (Gölge, 1997;Sakallı-Uğurlu et al, 2007;Yılmaz & Oskay, 2019;Karaman, 2022). Men's efforts to justify sexual violence and women's efforts to make it accepted that they are strong is a special function of myths (Çamaş &Mete, 2016;Yılmaz &Oskay, 2022).…”
Section: Introductionmentioning
confidence: 94%
“…Sexual abuse is a major problem in all over the world as well as in our country. It has multiple dimensions and very unique clinical evaluation, examination and reporting processes of the medico -legal expertise system (1). Sexual abuse can be accompanied with physical force, threatening, horrifying, drugging and / or misuse of the consents such as the unable ones to give consent because of their underage and / or mental disease.…”
Section: Introductionmentioning
confidence: 99%